2003
DOI: 10.1590/s1516-35982003000100029
|View full text |Cite
|
Sign up to set email alerts
|

Processamento de milho (floculado vs. laminado a vapor) e adição de monensina para bezerras leiteiras, pré e pós-desmama precoce

Abstract: RESUMO -A suplementação de fontes de amido de maior digestibilidade e o uso de aditivos com atividade coccidiostática e promotora de crescimento podem melhorar o desempenho de bezerros leiteiros pré e pós desmama. O objetivo deste trabalho foi avaliar o efeito de concentrados contendo milho laminado a vapor ou floculado, com ou sem a adição de monensina, no consumo, ganho de peso e parâmetros sanguíneos de bezerras leiteiras, antes e após a desmama realizada a sexta semana de vida. Foram utilizadas 32 bezerras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
11
0
22

Year Published

2011
2011
2011
2011

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 29 publications
(30 reference statements)
2
11
0
22
Order By: Relevance
“…There were no significant treatment effects for plasma glucose concentration in any of the evaluated periods. Observed values are in agreement with those found in the literature for calves of similar age (Quigley and Bernard, 1992;Nussio et al, 2003a).Owing to the ruminal fermentation pattern modification, as a result of monensin supplementation, with higher propionate concentrations (McGuffey et al, 2001), a higher plasma glucose concentration was expected for calves fed starter containing the ionophore. Similarly, the direct supplementation of propionate via calcium propionate should have resulted in the same response, since propionate is the main glucose precursor in the liver (Bergman, 1990).…”
supporting
confidence: 89%
See 4 more Smart Citations
“…There were no significant treatment effects for plasma glucose concentration in any of the evaluated periods. Observed values are in agreement with those found in the literature for calves of similar age (Quigley and Bernard, 1992;Nussio et al, 2003a).Owing to the ruminal fermentation pattern modification, as a result of monensin supplementation, with higher propionate concentrations (McGuffey et al, 2001), a higher plasma glucose concentration was expected for calves fed starter containing the ionophore. Similarly, the direct supplementation of propionate via calcium propionate should have resulted in the same response, since propionate is the main glucose precursor in the liver (Bergman, 1990).…”
supporting
confidence: 89%
“…However, these effects would be seen only in animals with the rumen already developed. Nussio et al (2003a) also have not observed differences in plasma glucose concentration in calves fed starter with or without monensin.…”
Section: Resultsmentioning
confidence: 64%
See 3 more Smart Citations